Effects of Aggregate-to-Binder Ratio on Mechanical Performance of Engineered Geopolymer Composites with Recycled Rubber Aggregates - Yiwei Li; Shuzhuo Zhi; Ran Chai; Zhiying Zhou; Jiarui He; Zizhao Yao; Zhan Yang; Genquan Zhong; Yongchang Guo (Buildings)
This study investigates the development of a fully rubberized fine-aggregate engineered geopolymer composite (R-EGC) by replacing quartz sand with waste rubber particles (RPs). The influence of the rubber aggregate-to-binder mass ratio (A/B) on the performance of the R-EGC was systematically examined from both macroscopic and microscopic perspectives. Quantitative analysis of crack width and number was conducted using binarized image-processing techniques to elucidate the crack propagation patterns. Moreover, scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) were employed to analyze the interfacial transition zone (ITZ) between the rubber aggregates and the geopolymer matrix under varying A/B ratios, aiming to explore the underlying failure mechanisms of the R-EGC. The research results indicated that the flowability of the R-EGC decreased gradually with increasing A/B ratio. The flowability of R-0.1 was 73.5%, outperforming R-0.2 and R-0.3 (66% and 65%, respectively). R-0.1 achieved the highest compressive strength of 35.3 MPa (compared to 31.2 MPa and 28.4 MPa for R-0.2 and R-0.3, respectively). R-0.3 demonstrated the most effective crack-control capability, with a tensile strength of 3.96 MPa (representing increases of 11.9% and 3.7% compared to R-0.1 and R-0.2, respectively) and the smallest crack width of 104 μm (indicating reductions of 20.6% and 43.5% compared to R-0.1 and R-0.2, respectively). R-0.2 exhibited the best ductility, with an ultimate tensile strain of 8.33%. Microstructural tests revealed that the interfacial transition zone (ITZ) widths for R-0.1, R-0.2, and R-0.3 were 2.47 μm, 4.53 μm, and 1.09 μm, respectively. An appropriate increase in the ITZ width was found to be beneficial for enhancing tensile ductility, but it compromised the crack-control ability of the R-EGC, thereby reducing its durability. Overall, this study clarifies the fundamental influence of the A/B ratio on the mechanical performance of the R-EGC. The findings provide valuable insights for future research in this field.